Analisis Pembiayaan COVID-19 di RSUP dr. Kariadi Semarang - yuliana setyarini; Chriswardani Suryawati; Septo Pawelas Arso (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
The cost of COVID-19 services can be a burden in itself that can affect hospital budgets. Services for COVID-19 patients at RSUP dr. Kariadi has so far been running well and smoothly, but there is no detailed data and information regarding COVID-19 financing, the process of submitting a COVID-19 financing claim and its implications for finances and services as well as leadership policies at RSUP dr. Kariadi so that activities are needed to analyze the costs of COVID-19. The purpose of the study was to analyze the financing of COVID-19, the process of submitting a claim for COVID-19 and its implications for finance and services as well as leadership policies at RSUP dr. Kariadi. The research approach used in this research is descriptive. Collecting data through document observation and interviews. The sample was selected using simple random sampling and the sample size was using the Slovin formula. The results showed that there was a negative difference of Rp.-1,832,258.63 between the average real cost of COVID-19 services and those claimed for outpatients, and there was a positive difference of Rp.61,695,327.45 for inpatients. The difference is caused by the claim system using cost per day. The biggest real cost component is the cost of laboratory examinations. The process for submitting a COVID-19 claim is in accordance with applicable regulations and all submissions declared eligible and paid. From the results of the Chi-Square test, it can be seen that there is no relationship between age and real costs in inpatient care and vice versa in outpatient care, length of days of treatment affects real costs, there is a relationship between comorbidities and real costs in SL3 and SL2, and there is no the relationship between co-morbidities with real costs in SL1 and outpatient. COVID-19 has caused the number of hospital visits and revenues in general to decline. Hospital leadership implemented several policies in dealing with the implications of COVID-19, including shifting budget posts, controlling services, zoning services, limiting non-COVID-19 patient services, transferring facilities and infrastructure, and optimizing the claim process. The research results are expected to be used as input in policy making and budget planning. Keywords: Financing Analysis, COVID-19